Étude préalable à la restauration d'un objet technico-scientifique contemporain - Rémy Geindreau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The Cockcroft-Walton Generator which powered with high voltage a particle accelerator, must be restored and presented on the campus of Lyon 1 University. How to approach its composite materiality and its gigantic size? The methods of an ethnologist as well as of a technologist are both necessary to carry out this survey which aims at best integrating the rupture between its past modes of existence and its patrimonial destiny.